Environmental Foundations to the Rise of Early Civilisations in China - Zhuang, Yijie (Cambridge University Press, 2025)
Holocene socioeconomic transformations in late-prehistoric China led to regional civilisations. This Element divides prehistoric China into Highlands, Lowlands, and Coastal, arguing that environmental conditions and subsistence adaptations fueled increased socioeconomic complexity. This title is also available as Open Access on Cambridge Core.